Civil engineering procedure (Thomas Telford, 2016)
'Civil Engineering Procedure' is an indispensable guide which describes and explains the stages of work for a project from the first consideration through to completion of construction and then beyond to handing over the resulting structures and services for use. The industry has evolved since the sixth edition in 2009 and this new fully updated edition includes coverage of the CDM 2015 Regulations, NEC3 and building information modelling (BIM).